Design of Control and Monitoring System to Avoid Inter-Ship Collisions in West Shipping Lane Tanjung Perak Surabaya - Sari, Devina P. (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
The occurrence of several ship accidents in narrow waters of Madura strait which is the west shipping lane of Tanjung Perak Surabaya has inspired the research on the design of a control system on the ship to avoid any collision between ships. The existence of automatic control with the autopilot is required to minimize the occurrence of collisions between ships In this final study investigated the application of fuzzy logic to control the yaw angle on the vessel MV Karana Sembilan. Fuzzy logic used is Sugeno Takagi type with the input of the error yaw, yaw rate and distance of the ship with a disturbance. Tests conducted with a control system without disturbance, with disturbance, and the presence of obstacles in front of the ship. Performance of control system is obtained by using the disturbance, the fuzzy appearance is 2:41 hm distance position, the speed of 7.5 knots and 0.5 error, then the resulting yaw angle is 6580. Results control with fuzzy syncronized with monitoring at M&C system in visual basic. The view of the monitoring, 3 types of scenarios obtained. For the first scenario, which is created with the control on it, produces the best results of the avoidance, if compared to the second scenario, with trajectory and control anti-collision cross, and if compared with the third scenario that has no built control system with decision-making on it.